A contribuição da ingestão aguda e moderada de cafeína para o desempenho cognitivo e tático de jogadores de futebol profissional - Almeida, Rodrigo Freire de (2020)
The football game and its complexity basically comprise tactical-technical activities, in which all the demands of the match or training requirements, from the players, strong answers to overcome the challenges faced by the game. These environmental deman